Computers and Games 6th International Conference, CG 2008, Beijing, China, September 29 - October 1, 2008. Proceedings - Herik, H. Jaap van den.; Xu, Xinhe; Ma, Zongmin; Winands, Mark H. M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 6th International Conference on Computers and Games, CG 2008, held in Beijing, China, in September/October 2008 co-located with the 13th Computer Olympiad and the 16th World Computer-Chess Championship. The 24 revised full papers presented were carefully reviewed and selected from 40 submissions. The papers cover all aspects of artificial intelligence in computer-game playing dealing with many different research topics, such as cognition, combinatorial game theory, search, knowledge representation, and optimization.
Single-Player Monte-Carlo Tree Search -- Amazons Discover Monte-Carlo -- Monte-Carlo Tree Search Solver -- An Analysis of UCT in Multi-player Games -- Multi-player Go -- Parallel Monte-Carlo Tree Search -- A Parallel Monte-Carlo Tree Search Algorithm -- Using Artificial Boundaries in the Game of Go -- A Fast Indexing Method for Monte-Carlo Go -- An Improved Safety Solver in Go Using Partial Regions -- Whole-History Rating: A Bayesian Rating System for Players of Time-Varying Strength -- Frequency Distribution of Contextual Patterns in the Game of Go -- A New Proof-Number Calculation Technique for Proof-Number Search -- About the Completeness of Depth-First Proof-Number Search -- Weak Proof-Number Search -- Cognitive Modeling of Knowledge-Guided Information Acquisition in Games -- Knowledge Inferencing on Chinese Chess Endgames -- Learning Positional Features for Annotating Chess Games: A Case Study -- Extended Null-Move Reductions -- GTQ: A Language and Tool for Game-Tree Analysis -- Probing the 4-3-2 Edge Template in Hex -- The Game of Synchronized Domineering -- A Retrograde Approximation Algorithm for Multi-player Can$1 (Bt Stop -- AWT: Aspiration with Timer Search Algorithm in Siguo.s
Keywords: Computer science; Data structures (Computer science).; Algorithms; Numerical analysis; Computer science -- Mathematics; Mathematical statistics; Artificial intelligence; Computer Science; Discrete Mathematics in Computer Science; Numeric Computing; Probability and Statistics in Computer Science; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Data Structures; Electronic books